Flow perfusion rate modulates cell deposition onto scaffold substrate during cell seeding - Campos Marín, A.; Brunelli, M.; Lacroix, D. (Biomechanics and modeling in mechanobiology, 2018)
The combination of perfusion bioreactors with porous scaffolds is beneficial for the transport of cells during cell seeding. Nonetheless, the fact that cells penetrate into the scaffold pores does not necessarily imply the interception of cells with scaffold substrate and cell attachment. An in vitro perfusion system was built to relate the selected flow rate with seeding efficiency. However, the in vitro model does not elucidate how the flow rate affects the transport and deposition of cells onto the scaffold. Thus, a computational model was developed mimicking in vitro conditions to identify the mechanisms that bring cells to the scaffold from suspension flow. Static and dynamic cell seeding configurations were investigated. In static seeding, cells sediment due to gravity until they encounter the first obstacle. In dynamic seeding, 12, 120 and 600 μ l/min flow rates were explored under the presence or the absence of gravity. Gravity and secondary flow were found to be key factors for cell deposition. In vitro and in silico seeding efficiencies are in the same order of magnitude and follow the same trend with the effect of fluid flow; static seeding results in higher efficiency than dynamic perfusion although irregular spatial distribution of cells was found. In dynamic seeding, 120 μ l/min provided the best seeding results. Nevertheless, the perfusion approach reports low efficiencies for the scaffold used in this study which leads to cell waste and low density of cells inside the scaffold. This study suggests gravity and secondary flow as the driving mechanisms for cell-scaffold deposition. In addition, the present in silico model can help to optimize hydrodynamic-based seeding strategies prior to experiments and enhance cell seeding efficiency.